Infernal Affairs Trilogie - Wai Keung Lau; Siu Fai Mak; Lai Yiu Fai; Leung, Tony; Lau, Andy; Wong, Anthony (Nameless-Media GmbH, 2017)
"Infernal Affairs" is a series of three crime-action films directed by Andrew Lau and Alan Mak, starring Andy Lau and Tony Leung. It tells the story of a police officer who infiltrates the triads, and a police officer secretly working for the same gang ... "Infernal Affairs" unites four of Hong Kong's top Best Actor award winners (Andy Lau, Tony Leung, Anthony Wong and Eric Tsang) which have led to public anticipation before release. The film's clever layout, compact plot, wonderful acting of the cast, excellent photography and music as well as popular dialogues are the main reasons that the first film won numerous awards and grossing over HK$50 million Hong Kong box office. [en.wikipedia.org]
Keywords: Blu-Ray-Disc